From Disconnected to Superagers: Perceived Quality of an Intergenerational Digital and Health Literacy Program for Central-Italy Older Adults - Esposito, Maurizio; Petroccia, Sara; Balestrieri, Fabiola (Italian Sociological Review, 2026)
This article examines the perceived quality of an intergenerational digital and health literacy program for Italian older adults, developed within the PRIN PNRR 2022 project Ageing, Health Literacy and Digital Skills through the Pandemics. Drawing on qualitative and quantitative data from semi-structured interviews (N = 21) and pre- and post-course questionnaires (N = 60), the study explores how older participants experienced learning processes, relational exchanges, and transformations in self-efficacy throughout the training. Adopting a grounded and interpretive approach, the analysis reconstructs participants’ trajectories from digital disconnection to varying forms of empowerment, identifying persistent barriers, enabling conditions and symbolic shifts in the perception of technology. Findings reveal that the program’s perceived quality depends less on technical proficiency than on relational and communicative dynamics that foster trust, recognition and continuity. Digital and health literacy emerge as intertwined dimensions of empowerment, extending beyond instrumental learning to encompass cultural adaptation and social participation. The study proposes the metaphor of the digital spore to describe the latent yet resilient nature of older adults’ competences, which can reactivate under supportive social and communicative conditions. Overall, the findings highlight how intergenerational communication functions as a generative engine of empowerment, transforming digital inclusion into a shared cultural practice that redefines ageing, care, and citizenship in the digital era.